Geostatistical Analysis of Zinc Fractions in Surface Soil of Alluvial Plains - Grewal, M S; Raman, R S; Dahiya, L S (Annals of Arid Zone, 2016)
Spatial variability of exchangeable zinc (Ex-Zn) and carbonate zinc (Carb-Zn) was investigated in 5600 km2 area of Rohtak and parts of its adjoining districts in the Indo-Gangetic alluvial plains of north-west India. Seventy two surface samples (0-15 cm) were taken at the nodes of a 10 km x 10 km grid. The semi variogram of Ex-Zn showed that this zinc fraction is spatialy dependent up to a distance of 30 km within the study area. and therefore, should be used for interpolation by kriging techniques. The semivariogram of Carb-Zn showed no spatial dependence of this fraction. indicating its random distribution. Hence, the semivariogram of Ex-Zn was used for interpolation of values between the grids by point and block kriging. The observed and kriged values were used to draw isarithmic maps of Ex-Zn. The estimation variance obtained by block kriging was 7.5 times less than that obtained by point kriging. As a result of this the isarithmic map by block kriging was a smooth one and that by point kriging was spotty. and the estimated number of samples required for Ex-Zn at 95% confidence level with a precision of Â± 10% of the true mean was only 6 by block krigning as compared, to 57 by point kriging.